Improving Lecturer Competence to Encourage Innovation and Creativity in Learning - Riza, Syahrul; Syarif, Muhammad; Mardatillah, Fuadi; Salam, Abdul Jalil; Khafidah, Wahyu; Yusuf, M. (SCAD Independent, 2024)
This research aimed at identifying the challenges faced by higher education institutions, particularly in terms of the quality of educational staff such as lecturers and exploring efforts that can be undertaken to enhance lecturer competence in supporting the quality of higher education. This study employed a qualitative research method with a descriptive approach. The subject of this research was the Universitas Islam Negeri Sumatera Utara. Data collection techniques involved observation and interviews with the university's leadership, faculty deans, program directors, and lecturers. Meanwhile, data analysis in this study was carried out cyclically, consisting of three simultaneous activities: data reduction, data presentation, and drawing conclusions or verifying the data. The findings revealed several challenges in enhancing lecturer competence, such as rapid technological changes, student diversity, and balancing teaching, research, and administrative duties. However, various efforts have been made to address these challenges. The higher education institution has launched competency development programs encompassing training, academic mentoring, relevant curriculum development, and industry collaboration. Improving lecturer competence will benefit students and the institution, help accelerate the overall development of higher education institutions, and help achieve national development goals.